POTENSI WILAYAH PENGEMBANGAN PETERNAKAN KAMBING LOKAL DI KECAMATAN PESISIR SELATAN KABUPATEN PESISIR BARAT - R M Sari; Z Zairiful; A Sofiana (Politeknik Negeri Lampung, 2022)
Development of local goat farming in Kecamatan Pesisir Selatan, Kabupaten Pesisir Barat, the potential includes suitability of temperatur, climate, feed, labor. This reseach has been conducted on July – August 2021. Analysis used Location Quotient to determine the basic sector and non basic sector. The variablees observed in this study were populaion of goat and ruminants, the availability of social-cultural forage 100% owner livestock ownership and natural condutions. The results of study show the fasibility of the area as a village an 9 villages which inclides sector basis and availability of forage 12.086,08 ton/BK/th. Based on the results of reseache, the Kecamatan Pesisir Selatan Kabupaten Pesisir Barat